New Approach Methodologies (NAMs) to assess killer whale (Orcinus orca) estrogen receptor alpha (ERα) transactivation potencies by DDTs and their risks - Dave Arthur R. Robledo; Takahito Kumagawa; Mari Ochiai; Hisato Iwata (Ecotoxicology and Environmental Safety)
Killer whales (Orcinus orca), as apex predators, accumulate high levels of persistent organic pollutants (POPs) such as dichlorodiphenyltrichloroethane and its analogs (DDTs) and face their risks at the population level. The assessment of the function of estrogen receptor alpha (ERα) is crucial for evaluating impact of DDTs on killer whale endocrine and reproductive health. However, due to ethical constraints, little is known about the effects of DDTs on the function of killer whale ERα (kwERα). This study aimed to assess kwERα transactivation potencies in response to various DDTs (p,p′-DDT, o,p′-DDT, p,p′-DDD, o,p′-DDD, p,p′-DDE, o,p′-DDE, and p,p′-DDOH) by New Approach Methodologies (NAMs). We constructed an in vitro kwERα-expressed reporter gene assay and measured transactivation potencies of DDTs as the 10 % effective concentration (REC10) relative to the maximum response to 17β-estradiol exposure. We also employed in silico approaches such as molecular docking and protein-ligand network analysis (PLNA) to elucidate the interaction of kwERα protein and DDTs. The in vitro results revealed an estrogenic potency in the order of 17β-estradiol > o,p’-DDT > o,p’-DDE > o,p’-DDD > p,p’-DDD > p,p’-DDOH > p,p’-DDT > p,p’-DDE (no activity). Strong positive correlations were found between in vitro REC10 values and in silico docking scores, suggesting the structure-activity relationship of the estrogenic potencies of DDTs to kwERɑ. PLNA highlighted contribution of Glu353 and Phe404 in kwERα as essential residues to the interaction with DDTs. Risk assessments indicated that the o,p’-DDT-estrogenic equivalency quantities of DDTs in the blubber of both Irish and Canadian Arctic killer whales exceeded the in vitro REC10 of o,p’-DDT, suggesting a significant risk of kwERα-mediated endocrine disruption in these populations. These findings underscore the importance of NAMs including in vitro and in silico approaches for assessing the endocrine and reproductive risk in killer whales.